Cytocompatible and osteoconductive silicon oxycarbide glass scaffolds 3D printed by DLP: a potential material for bone tissue regeneration - Carnieri, Matheus Versão; Garcia, Daniele de Freitas; Voltolini, Rafael; Volpato, Neri; Mafra, Marcio; Bernardelli, Euclides Alexandre; Stimamiglio, Marco Augusto; Rebelatto, Carmen Kuniyoshi; Correa, Alejandro; Berti, Lucas Freitas; Marcon, Bruna Hilzendeger (Frontiers in Bioengineering and Biotechnology, 2024)
Bone lesions affect individuals of different age groups, compromising their daily activities and potentially leading to prolonged morbidity. Over the years, new compositions and manufacturing technologies were developed to offer customized solutions to replace injured tissue and stimulate tissue regeneration. This work used digital light processing (DPL) technology for three-dimensional (3D) printing of porous structures using pre-ceramic polymer, followed by pyrolysis to obtain SiOC vitreous scaffolds. The SiOC scaffolds produced had an amorphous structure (compatible with glass) with an average porosity of 72.69% ± 0.99, an average hardness of 935.1 ± 71.0 HV, and an average maximum flexural stress of 7.8 ± 1.0 MPa, similar to cancellous bone tissue. The scaffolds were not cytotoxic and allowed adult stem cell adhesion, growth, and expansion. After treatment with osteoinductive medium, adult stem cells in the SiOC scaffolds differentiated to osteoblasts, assuming a tissue-like structure, with organization in multiple layers and production of a dense fibrous matrix rich in hydroxyapatite. The in vitro analyses supported the hypothesis that the SiOC scaffolds produced in this work were suitable for use as a bone substitute for treating critically sized lesions, with the potential to stimulate the gradual process of regeneration of the native tissue. The data obtained stimulate the continuity of studies with the SiOC scaffolds developed in this work, paving the way for evaluating safety and biological activity in vivo.